THE EFFECT OF ENVIRONMENTAL, SOCIAL, AND GOVERNANCE (ESG) DISCLOSURE AND ENVIRONMENTAL PERFORMANCE ON STOCK RETURN - Farhan Aziz; Anis Chariri (Diponegoro Journal of Accounting, 2023)
This study examines the effect of environmental, social, and governance (ESG) disclosure and environmental performance on stock returns. Environmental, social, and governance (ESG) disclosure independent variables are projected through the ESG Disclosure Score, while environmental performance is assessed through the PROPER Rating. The dependent variable uses stock returns. The population comprises non-financial companies listed on the Indonesia Stock Exchange (IDX) during 2017-2021. The sampling technique used in this study was a purposive sampling method with specific criteria, resulting in 75 samples of non-financial companies being examined. Data analysis was performed using multiple linear regression. The analysis results show that environmental performance significantly positively affects stock returns, and environmental, social, and governance (ESG) disclosure has no significant adverse effect.